2020
DOI: 10.1017/s1751731120001597
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inorganic phosphate supplementation on egg production in Hy-Line Brown layers fed 2000 FTU/kg phytase

Abstract: Phytase has long been used to decrease the inorganic phosphorus (Pi) input in poultry diet. The current study was conducted to investigate the effects of Pi supplementation on laying performance, egg quality and phosphate–calcium metabolism in Hy-Line Brown laying hens fed phytase. Layers (n = 504, 29 weeks old) were randomly assigned to seven treatments with six replicates of 12 birds. The corn–soybean meal-based diet contained 0.12% non-phytate phosphorus (nPP), 3.8% calcium, 2415 IU/kg vitamin D3 and 2000 F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…However, most of the works reviewed in the literature show that the main determinant of the quality of the shell is the level of Ca and not so much the level of P. Bar et al [ 55 ] already observed that an increase in the Ca level produced a clear improvement in the shell weight, while the modifications of the P level had no effect. In fact, most of the studies that evaluated the effect of the inorganic P level, at a constant Ca level, did not observe any significant effect on the eggshell characteristics [ 29 , 32 , 36 , 56 ]. These results could explain why the PC diet allowed obtaining eggs with a greater shell thickness compared to NC diet, by providing a higher level of Ca, while the greater availability of P due to the inclusion of phytase did not lead to improvements in the shell quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the works reviewed in the literature show that the main determinant of the quality of the shell is the level of Ca and not so much the level of P. Bar et al [ 55 ] already observed that an increase in the Ca level produced a clear improvement in the shell weight, while the modifications of the P level had no effect. In fact, most of the studies that evaluated the effect of the inorganic P level, at a constant Ca level, did not observe any significant effect on the eggshell characteristics [ 29 , 32 , 36 , 56 ]. These results could explain why the PC diet allowed obtaining eggs with a greater shell thickness compared to NC diet, by providing a higher level of Ca, while the greater availability of P due to the inclusion of phytase did not lead to improvements in the shell quality.…”
Section: Discussionmentioning
confidence: 99%
“…Hughes et al [ 7 ] found that phytase addition to a deficient diet did not affect bone ash percentage at 42 weeks of age, but it was significantly improved at 61 weeks of age. In any case, there are already several studies indicating that, when enough phytase is introduced in the feed (2000 FTU/kg), the level of aP is not a limiting factor for the bone structure of laying hens in the long term [ 29 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jing et al [ 29 ] indicated that tibial weight, tibial ash, calcium percentage, and phosphorus percentage were not different for Lohmann White laying hens from 22 weeks to 34 weeks of age fed various levels of NPP if phytase at 1000 FTU/kg was added to the diet. Cheng et al [ 30 ] reported that 0.12% NPP in a basal diet (without inorganic phosphate) did not cause significant changes in the tibiae of Hy-Line Brown laying hens from 29 weeks to 40 weeks of age with supplementation of phytase at 2000 FTU/kg. In general, for laying hens, there is no need to add inorganic phosphate to a diet containing phytase [ 9 , 24 , 30 ]; our data did not seem to confirm this view.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al [ 30 ] reported that 0.12% NPP in a basal diet (without inorganic phosphate) did not cause significant changes in the tibiae of Hy-Line Brown laying hens from 29 weeks to 40 weeks of age with supplementation of phytase at 2000 FTU/kg. In general, for laying hens, there is no need to add inorganic phosphate to a diet containing phytase [ 9 , 24 , 30 ]; our data did not seem to confirm this view. Tibial breaking strength, tibial ash, and phosphorus content were significantly lower in the group without inorganic phosphate (dietary NPP level = 0.12%) compared with the group with NPP supplementation of 0.15–0.30% (dietary NPP level = 0.27–0.42%).…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorus content of the excreta samples was determined colorimetrically with ammonium-vanadium-molybdate using a UV-1800 spectrophotometer (Shimadzu, Japan) ( Ren et al., 2017 ). Calcium content of the excreta samples was analyzed with a Z-2000 flame atomic absorption spectrophotometer (Hitach, Japan) ( Cheng et al., 2020 ). Percent phosphorus and calcium concentrations in the excreta samples are presented as air dried basis, and 24-h total excretion of phosphorus and calcium were calculated accordingly.…”
Section: Methodsmentioning
confidence: 99%